“Guardians of tradition”. Resistances to the political and socio cultural change during the late Francoism and the transition to democracy in Eastern Andalusia - Román Ruiz, Gloria (Hispania Nova, 2020)
The article wonders about the nature and the intensity of the resistances set in motion by some social groups against the process of political and socio-cultural transformation that began at the end of the sixties and extended throughout the seventies. It pays attention to those subjects who raised their voice in defence of the tradition and against the modernity, as well as to the impact of their actions and opposition behaviours on the process of democratization. In the first place, the paper deals with the actions of resistance activated by the conservative parishioners who had acquiescent political attitudes towards the dictatorship and who attended to a parish ruled by a progressive priest. Secondly, it focuses on the resistances expressed by the parochial community of the San José church (Estepona, Málaga) caused by a nudist project in the town in 1978.
Keywords: late Francoism; transition to democracy; democratization; resistances to change; conservatism